Irreversible Electroporation in Interventional Oncology: Where We Stand and Where We Go - Savic, L. J.; Chapiro, J.; Hamm, B.; Gebauer, B.; Collettini, F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Irreversible electroporation (IRE) is the latest in the series of image-guided locoregional tumor ablation therapies. IRE is performed in a nearly non-thermal fashion that circumvents the „heat sink effect“ and allows for IRE application in proximity to critical structures such as bile ducts or neurovascular bundles, where other techniques are unsuitable. IRE appears generally feasible and initial reported results for tumor ablation in the liver, pancreas and prostate are promising. Additionally, IRE demonstrates a favorable safety profile. However, site-specific complications include bile leaking or vein thrombosis and may be more severe after pancreatic IRE compared to liver or prostate ablation. There is limited clinical evidence in support of the use of IRE in the kidney. In contrast, pulmonary IRE has so far failed to demonstrate efficacy due to practicability limitations. Hence, this review will provide a state-of-the-art update on available clinical evidence of IRE regarding feasibility, safety and oncologic efficacy. The future role of IRE in the minimally invasive treatment of solid tumors will be discussed.Key points:• Preclinical findings of IRE have been successfully translated into clinical settings.• Non-thermal ablation is able to prevent the "heat sink effect" and collateral damage.• IRE should primarily be applied to tumors adjacent to sensitive structures (e. g. bile ducts).IRE efficacy appears promising in the liver, pancreas and prostate with tolerable morbidity.• In contrast, there are no evidential benefits of IRE in the lung parenchyma.Citation Format:• Savic LJ, Chapiro J, Hamm B et al. Irreversible Electroporation in Interventional Oncology: Where We Stand and Where We Go. Fortschr Röntgenstr 2016; 188: 735 – 745
Keywords: irreversible electroporation; pancreas; lung; prostate; liver; kidney; safety; interventional procedures; treatment effects; abdomen; thorax; ablation procedures; ablation